Study of Seed Germination in Tulang Cikal (Entada phaseoloides) Merr. - Ketut Arinasa, Ida Bagus; Warseno, Tri (Proceeding International Conference on Global Resource Conservation, 2013)
Tulang cikal (Entada phaseoloides Merr.) is one of the Bali Botanical Gardenâs plant collections which have medicinal properties and are used by the Balinese as a ceremonial plant. The purpose of this study was to determine the appropriate seed germination techniques in an attempt to ex-situ conservation of tulang cikal (E. phaseoloides Merr.). The experiments were performed using 2 treatments, that treatment of seeds and types of media. Treatment of seed coats covering grinding, soaking the seeds in hot water, and without treatment (control). While the media used in the treatment is sand and humus medium. The experiments were performed with 3 replications; each replication consisted of four pots. The parameters observed were percentage of seed germination, height / stem length, number of leaves and leaf area. Based on the results of the experiment, showed that seed can only germinated on grinding treatment, the percentage of seeds that grow seed-highest average in the medias treatment of humus that is 66.66%. The best combination treatment is coat grinded seeds and planted in sand medium with high / average stem length 305.44 cm, number of leaves 22.55 sheets, and leaf area average 28, 83 cm2. The results of this research can be used as a reference for plant propagation in the ex-situ conservation of tulang cikal (E. phaseoloides Merr.).